Urban Life Experiences of Syrians in Turkey: The Cases of Gaziantep and Izmir - Sait Vesek; Nadir Suğur (İnsan & Toplum)
The civil war in Syria resulted in a massive population influx into the neighboring countries since 2011. Geographical proximity of Turkey and its position as a gateway to Europe have made Turkey a host country for most Syrians refugees. Prolonging civil war in Syria and difficulties to get access to Europe compelled them to stay in Turkey. The reason why they have settled down in certain cities and difficulties that they have encountered in their everyday life merit attention to understand the very issue of refugee problems in Turkey. On that purpose, we conducted a sociological research on Syrians who settled in Gaziantep and İzmir. This paper tries to examine the degree to which Syrians are integrated into the local labour market and problems that Syrians endure in everyday life activities. The research is drawn from a fieldwork conducted on 30 semi-depth interviews in Gaziantep and 27 in İzmir. The results show that the reasons for Syrian to make a living in Gaziantep are its proximity to Syria, cultural familiarity and opportunities for Syrians entrepreneurs to do business. As for İzmir, Syrians stated its closeness to Europe, availability of jobs and better life prospect.